Orginal article Lectin binding pattern in meningiomas of various histological subtypes - Taraszewska, Anna; Matyja, Ewa (Folia Neuropathologica, 2007)
Altered tumour cell glycosylation in relation to cellular heterogeneity in human brain tumours remains relatively unexplored. It has been reported that meningiomas express variability in glycosylation properties; however only limited meningioma subtypes have been studied with lectins histochemistry. The aim of this study was to compare the binding pattern of biotinylated lectins in seven subtypes of histologically benign intracranial meningiomas (meningothelial, transitional, fibroblastic, psammomatous, secretory, microcystic and angiomatous types). The study was performed on biopsy material of 30 cases of meningiomas with different lectins: Peanut agglutinin (PNA), Soybean agglutinin (SBA), Dolichos biflorus agglutinin (DBA), Wheat germ agglutinin (WGA), Cocanavalin A (Con A) and Ulex europaeus agglutinin 1 (UEA-1). The expression of lectin-binding glycoconjugates exhibited differences between certain subtypes of meningiomas. WGA with affinity for GlcNAc and neuraminic acid labelled the cells of all meningiomas but most intensely those of fibroblastic type. Staining with PNA, SBA and DBA, which are GalNAc specific, varied from negative to strongly positive. Enhanced PNA reactivity reflected mainly cytoarchitectural pattern of tumour growth, such as syncytial lobules, whorled formations or trabecular arrangements of meningioma cells. DBA labelled the majority of cellular nuclei. SBA showed binding to psammoma bodies, while pseudopsammoma bodies were stained with PNA, WGA, Con A, and to a lesser extent with SBA and DBA. The secretory meningiomas exhibited strong and heterogeneous lectins reactivity within pseudopsammoma bodies whereas the neoplastic cells were only occasionally stained. The selective reactivity of UEA-1 with endothelial cells of blood vessels resulted in a specific visualisation of the vascular network in all histological subtypes of meningiomas. These results documented the heterogeneous glycosylation pattern in different subtypes of meningiomas and indicate the usefulness of lectins in the evaluation of pluripotential differentiation of meningioma cells.